Uncoupling Molecular Testing for SARS-CoV-2 From International Supply Chains - Stanton, Jo-Ann L.; O'Brien, Rory; Hall, Richard J.; Chernyavtseva, Anastasia; Ha, Hye Jeong; Jelley, Lauren; Mace, Peter D.; Klenov, Alexander; Treece, Jackson M.; Fraser, John D.; Clow, Fiona; Clarke, Lewis; et al. (Frontiers in Public Health, 2022)
The rapid global rise of COVID-19 from late 2019 caught major manufacturers of RT-qPCR reagents by surprise and threw into sharp focus the heavy reliance of molecular diagnostic providers on a handful of reagent suppliers. In addition, lockdown and transport bans, necessarily imposed to contain disease spread, put pressure on global supply lines with freight volumes severely restricted. These issues were acutely felt in New Zealand, an island nation located at the end of most supply lines. This led New Zealand scientists to pose the hypothetical question: in a doomsday scenario where access to COVID-19 RT-qPCR reagents became unavailable, would New Zealand possess the expertise and infrastructure to make its own reagents onshore? In this work we describe a review of New Zealand's COVID-19 test requirements, bring together local experts and resources to make all reagents for the RT-qPCR process, and create a COVID-19 diagnostic assay referred to as HomeBrew (HB) RT-qPCR from onshore synthesized components. This one-step RT-qPCR assay was evaluated using clinical samples and shown to be comparable to a commercial COVID-19 assay. Through this work we show New Zealand has both the expertise and, with sufficient lead time and forward planning, infrastructure capacity to meet reagent supply challenges if they were ever to emerge.